Islam, Asymmetric Policy, and Social Conflict: The State's Role as a Root of Radicalism in the Philippines and Thailand - Bayu Mitra A. Kusuma (Center for Southeast Asian Social Studies (CESASS), 2017)
Radicalism has become a serious problem for many countries, including in Southeast Asia. One of its triggering factors is an extreme understanding of religion that leads to the assumption that people with different understandings are wrong and that violence is a legitimate way to change the situation. This often occurs because of a love of lineage or clan, as well as aggressive instincts. Such an extreme understanding results in the religious social conflicts, which in reality—particularly those involving Islam in Southeast Asia—are often influenced by regimes’ asymmetric policies. This study, therefore, explores the role of the State as a root of radicalism in the context of the dynamic relationship between Islam and asymmetric policies, with a focus on the southern Philippines and Thailand. Research findings show that the rise of radicalism in the Philippines was caused by social conflict resulting from government manipulation of referendum policy on special autonomy in predominant Muslim areas. Meanwhile, radicalism in Thailand was triggered by social conflict resulting from the cultural assimilation policy imposed upon the Muslim community by the government.